KARAKTERISTIK KLINIKOPATOLOGI DAN IMUNOHISTOKIMIA PENDERITA KARSINOMA PAYUDARA DI RUMAH SAKIT UMUM PUSAT SANGLAH DENPASAR BALI TAHUN 2017-2018 - Kadek Dwi Pradnyawati; I Gusti Ayu Sri Mahendra Dewi; Ni Made Mahastuti; Ni Putu Sriwidyani (E-Jurnal Medika Udayana, 2021)
Breast carcinoma is a malignant disease with high cases in Indonesia. According to the World Health Organization, 21.4% of total deaths in women due to malignancy in Indonesia are caused by breast cancer. In establishing the diagnosis of breast carcinoma, histopathology and immunohistochemistry examinations are important. The results of histopathological images and immunohistochemistry examinations have significant implications for treatment options and prognosis for breast carcinoma. This research aimed at determining the clinicopathology and immunohistochemistry characteristics of breast carcinoma sufferers at the RS Umum Pusat Sanglah Bali in the period 2017-2018. The study method was conducted with a descriptive cross-sectional studies. Variable sample data were selected from inclusion and exclusion criteria. Data were analyzed using SPSS version 20 software to obtain clinicopathology characteristics based on age, lateralization, histopathology type, grade, and immunohistochemistry characteristics in the form of luminal A, luminal B, HER-2 positive, and triple-negative subtypes. The results showed that most patients with breast carcinoma at RS Umum Pusat Sanglah Bali in the period 2017-2018 occurred in the 41 - 50 years range of 39,1%, with the dominant lateralization being the left breast (52,5%). The most histopathology type was Invasive Carcinoma of No Special Type at 86,6% with the most characteristic grade was grade II at 47,0%, and the most immunohistochemistry subtype was luminal B (49,5%). Keywords: Breast Carcinoma, Characteristics, Clinicopathology, Immunohistochemistry